Chemical similarities and differences among inhibitors of nitric oxide synthase, arginase and dimethylarginine dimethylaminohydrolase-1: Implications for the design of novel enzyme inhibitors modulating the nitric oxide pathway. (15th October 2022) - Doman, Anthony J.; Tommasi, Sara; Perkins, Michael V.; McKinnon, Ross A.; Mangoni, Arduino A.; Nair, Pramod C.
Graphical abstract: Abstract: Nitric oxide (NO) is a signalling molecule that controls a multitude of regulatory functions including neurotransmission, vascular tone, immune response, and angiogenesis. Regulating NO concentrations in cells using small molecules is an active area of research in the treatment of several pathologies such as cardiovascular disease, cancer, and inflammatory conditions. Small molecule-inhibition of critical NO regulatory enzymes, NO synthase (NOS), arginase, and dimethylarginine dimethyaminohydrolase-1 (DDAH1), has shown therapeutic benefits as well as limitations and is a focus of current research. In recent years, DDAH1 has been explored as a potential target to indirectly regulate NO in diseases characterized by excessive NO production. This review discusses the biological and pathophysiological role of the NO pathway, the existing inhibitors of NOS, arginase and DDAH1, and the conventional and structure-guided structure–activity relationship studies involved in their discovery. The key structural elements of amino acid-derived inhibitors responsible for selective inhibition of each enzyme, and the chemical features responsible for dual enzyme inhibition are also discussed. Finally, a synthetic scheme for developing both selective and dual inhibitors using common starting materials is provided, offering unique insights in the quest for the rational design of novel NO pathway inhibitors.